Exploring Linguistic Sexism in Students Written Academic Discourse of Department English at KUST - Saqib Raza; Dr. Mahwish Mumtaz Niazi; Muhammad Hamza (Dialogue Social Science Review (DSSR), 2025)
The present study examines linguistic sexism within the academic discourse of BS English students at Kohat University of Science and Technology (KUST), employing a mixed-method approach that integrates both quantitative and qualitative research techniques. This methodology enables a thorough analysis of the extent and impact of gender biases in language use, particularly focusing on the use of pronouns and nouns. The quantitative analysis scrutinized written passages from 92 students on the topic "Duties of a Student," revealing a significant preference for masculine pronouns and a complete absence of feminine pronouns, highlighting a prevalent normative gender bias. Conversely, the qualitative component involved focused group discussions with 14 representative students, exploring their awareness and perceptions regarding feminist linguistic reforms and the use of gender-neutral language. The findings indicate substantial gaps in the adoption of non-biased language, underlining the strong influence of entrenched gender norms on language choices. The study concludes that there is a critical need for educational reforms aimed at promoting gender-neutral language practices, which would challenge the patriarchal norms deeply embedded even within educated communities.